The symmetric syntax of Japanese complex verbs and Slavic prefixes - Endo, Yoshio; Wiland, Bartosz (Tokyo: Hituzi, 2014)
We report on a robust symmetry between the Polish and the Japanese sequence of syntactic projections in what superficially looks like different domains, namely verbal prefixes (Polish) and multiple verbs (Japanese). This paralellism strongly supports the thesis about the finegrained sequence of positions in syntax, namely that there exists the functional sequence of syntactic heads (fseq) which is invariantly ordered by UG (see e.g. Cinque (1999)) and the surface differences among particular langauges in the order of elements that instantiate this fseq result solely from movement (not from the variation in fseq itself).